2018
DOI: 10.1002/jcb.27777
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharides promoted proliferation and differentiation in osteoblasts

Abstract: Osteoblasts have the capacity to differentiate into several different cell types, including adipocyte, chondrocyte, and muscle lineages. Therefore, osteoblast can be potentially applied in the treatment of bone diseases. The factors controlling osteoblast differentiation is complex. Recently, it has been reported that some natural products regulate the differentiation in osteoblasts and promote bone formation. Based on these findings, this study demonstrated that Lycium barbarum polysaccharides (LBP) could pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Thus, upregulation of PCNA and OCN along with morphological observation clearly indicate the proliferative effects of LG. These results are in accordance with the previous studies on increased proliferation with number of herbs [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Thus, upregulation of PCNA and OCN along with morphological observation clearly indicate the proliferative effects of LG. These results are in accordance with the previous studies on increased proliferation with number of herbs [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, many studies have shown that LBP can reduce the damage of free radicals to the organism by reducing the number of free radicals and enhancing the activity of antioxidant enzymes in the process of damage repair. Researchers have demonstrated that LBP can stimulate osteoblast proliferation (Chan et al, 2019), increase the expression of key proteins linked to cellular proliferation such as proliferating cell nuclear antigen (PCNA) and Ki67, and can also enhance the activation of osteogenesis‐related proteins including bone morphogenetic protein 2 (BMP2), bone gamma‐carboxyglutamate protein (BGP), secreted phosphoprotein 1 (OPN), and collagen type I alpha 1 chain (COL1A1) (H. Y. Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The above three samples were tested on calvarial osteoblasts from the rat/mice calvaria at postnatal day. The polysaccharides from L. barbarum [ 28 ], and three compounds including crocin [ 34 ], linarin via bone morphogenetic proteins 2(BMP-2)/runt-related transcription factor 2(Runx2) pathway [ 42 ], and ginsenoside Rb2 via a reduction of oxidative damage [ 20 ] were all tested on the osteoblast MC3T3‐E1 cell line. The results showed that osteoblast differentiation could be induced by the above extracts and compounds [ 18 , 20 , 28 , 30 , 33 , 34 , 42 ].…”
Section: In Vitro Studiesmentioning
confidence: 99%